Obtaining phenolic-enriched liquid fractions and compostable pomace for agriculture from alperujo using standard two-phase olive oil mill equipment - Rodríguez Márquez, Manuel (2024)
Olive oil extraction by two-phase systems generates a by-product called “alperujo” which presents several difficulties for its valorization. The present work evaluated an industrial approach, based on the application of thermal treatments to alperujo followed by solid/liquid separation using standard two-phase olive oil mill equipment. Treatments consisted of the thermo-malaxation of alperujo at 70 ◦C for 45 or 90 min, with or without acid addition, followed by solid/liquid separation in an industrial decanter. The solid was characterized concerning subsequent use for composting, while total and hydrophilic phenolics were analyzed in liquid for their recovery. Additionally, a laboratory-scale trial to compare phenolic purification by ethylic acetate extraction with chromato graphic procedures was also included. The static respiration index showed that solid fractions presented higher susceptibility to biodegradation processes than raw alperujo. The phenolic con tent of treated liquid fractions was higher than in raw alperujo. Total phenolics were maximum at the longest exposure time without acid addition, while hydrophilic phenolics were highest at the shortest exposure time in acidified samples. The use of non-ionic resins seemed attractive for obtaining highly concentrated phenolic fractions. The proposed thermal treatments can be applied in olive oil industries, allowing in situ pomace valorization and the recovery of phenolic-enriched liquid fractions.